Pengembangan Game Interaktif Berbasis Unity untuk Meningkatkan Kemampuan Matematika Anak - Prayuga Dwi Fatchuli; Eka Ardhianto (Pusat Riset dan Inovasi Nasional, 2026)
This study presents the development of an interactive educational game built using the Unity engine to enhance children’s mathematical abilities. The research was motivated by the low engagement and effectiveness of conventional mathematics learning methods. The Multimedia Development Life Cycle (MDLC) was employed, consisting of concept definition, interface design, asset collection, system assembly, testing, and distribution. The resulting game, Smart Adventure, provides arithmetic challenges (addition and subtraction) integrated into a 2D adventure environment with real-time feedback. System testing demonstrates high performance, including response times below 150 ms and 100% scoring accuracy based on confusion matrix evaluation. These findings indicate that interactive game-based media can significantly increase student motivation, focus, and conceptual understanding.